STABILITY TEST OF FACIAL MOISTURIZING CREAM FROM SNAIL SLIME (Achatina fulica) WITH VARIATIONS IN STEARIC ACID - Suhesti, Iin; Putri, Vania Santika; Hidayah, Dian Nurul (Tahta Media Group, 2025)
The skin is exposed to free radicals from the environment every day which can cause premature aging. The aging process is characterized by decreased sweat gland production, followed by decreased skin moisture due to reduced skin elasticity and the skin's ability to retain water, so the skin needs moisturizer. Snail slime (Achatina fulica) contains active substances glycosaminoglycan and allantoin with a concentration of 3% functioning as a tightener, softener and moisturizer for facial skin and contains achasin protein which has antibacterial activity against Propionibacterium acnes with an inhibitory power of 16.0 mm ± 2.6 at a concentration of 11%. This study aims to determine the effect of achasin protein on Propionibacterium acnes on skin elasticity.to know the variation of stearic acid concentration and stability of facial moisturizing cream from snail slime. This study used an experimental method with 3% snail slime as the active ingredient and stability testing was carried out using 2 methods, namely cycling test and centrifugation. Snail slime was formulated into a cream preparation with varying stearic acid concentrations of 5%, 7%, 9% and 11%. Based on the results of the stability test using the cycling test method, it was found that all cream formulas were physically stable because they did not experience phase separation, while based on the results of the stability test using the centrifugation method, it was found that the cream in formula 4 was more physically stable when compared to formulas 1, 2 and 3 because it experienced phase separation at the 150th minute. Conclusion: The resulting facial moisturizer cream was stable in the cycling test method but not stable in the centrifugation method.